KORELASI KADAR TROPONIN I DENGAN KADAR SERUM KALSIUM PADA SINDROMA KORONER AKUT: CORRELATION BETWEEN TROPONIN I LEVELS AND SERUM CALCIUM LEVELS IN ACUTE CORONARY SYNDROME - Hadiyatur Rahma (Jurnal Kedokteran STM (Sains dan Teknologi Medik), 2026)
Acute coronary syndrome (ACS) encompasses a spectrum of clinical conditions resulting from a sudden reduction in coronary blood flow, primarily due to rupture of an atherosclerotic plaque followed by intraluminal thrombus formation. It represents a cardiovascular emergency that requires prompt diagnosis and timely management to reduce morbidity and mortality. Advances in diagnostic technology have refined cardiac troponin assays, improving their sensitivity and specificity for detecting and quantifying cardiomyocyte injury. Calcium plays a critical role in multiple biological processes associated with cardiovascular disease, including platelet adhesion and aggregation, coagulation, enzymatic activity, myocardial contractility, and cardiomyocyte apoptosis. This study aimed to evaluate the correlation between troponin I levels and serum calcium levels in patients with ACS. A cross-sectional study was conducted at H. Adam Malik General Hospital, Medan, between February and March 2024. The study included 40 patients diagnosed with ACS who met the inclusion and exclusion criteria. Troponin I and serum calcium levels were measured in all participants. Statistical analysis was performed using Spearman’s correlation test. Among the 40 participants, the majority were aged over 55 years, predominantly male (72.5%), and 67.5% had a history of smoking. The median troponin I level was 6.09 ng/mL (range 0.12–15), while the median serum calcium level was 8.86 mg/dL (range 7.4–11.5). A weak and non-significant negative correlation was observed between troponin I and serum calcium levels (r = −0.133, p = 0.415). In conclusion, no significant correlation was found between troponin I levels and serum calcium levels in patients with ACS. AbstrakSindrom koroner akut (SKA) merupakan spektrum kondisi klinis yang disebabkan oleh penurunan aliran darah koroner secara tiba-tiba akibat ruptur plak aterosklerotik dan pembentukan trombus intraluminal. Kondisi ini merupakan kegawatdaruratan kardiovaskular yang membutuhkan diagnosis dan penanganan cepat untuk menurunkan angka morbiditas dan mortalitas Kemajuan teknologi telah menyempurnakan tes Troponin dan meningkatkan akurasinya dalam mendeteksi dan mengukur cedera kardiomiosit. Kalsium memainkan peran penting dalam banyak proses biologis yang berhubungan dengan penyakit kardiovaskular, termasuk adhesi dan agregasi trombosit, pembekuan darah, aktivitas enzimatik, kontraksi jantung, dan apoptosis kardiomiosit. Penelitian ini bertujuan untuk menganalisis korelasi kadar troponin I dengan kadar serum kalsium pada SKA. Penelitian ini menggunakan desain cross sectional di RSUP H.Adam Malik Medan dari Februari 2024-Maret 2024. Subjek dalam penelitian ini adalah 40 pasien yang terdiagnosa SKA yang memenuhi kriteria inklusi dan ekslusi. Pasien diperiksakan troponin I dan serum kalsium. Analisa data dengan korelasi Spearman. Dari subjek penelitian 40 pasien, sebagian besar subjek penelitian berusia diatas 55 tahun, sebagian besar adalah laki-laki (72,5%), riwayat merokok sebesar 67,5%. Kadar median troponin I 6,09 ng/ml (0,12-15). Kadar median kalsium 8,86(7,4-11,5) mg/dL. Terdapat korelasi negatif lemah dan tidak signifikan antara troponin I dengan kalsium (r = -0,133 , p = 0,415). Tidak terdapat korelasi antara troponin I dengan kalsium.